Analisis Implementasi Good Governance terhadap Pelayanan Publik pada Dinas Kependudukan dan Catatan Sipil Kota Palembang - Rauf, Abdul; Andriyani, Dwi (Jurnal Studi Pemerintahan dan Akuntabilitas, 2023)
Purpose: This study aims to determine how the influence of Good Governance on public services at the Office of Population and Civil Registration of Palembang City. Methodology: This  study  used  quantitative and qualitative methods with data collection applications using questionnaires and literaturestudy. Result: The results showed that there was a positive and significant relationship between the Good Gocernance variable and the Public Service variable. This can be seen from the results of statistical tests where the correlation coefficient r about 0.769, which means that there is a strong relationship between the two variables. The influence of each good governance variable stimulants are only able to affect the variable quality of public services by 27,7%, the remaining 72,3% is influenced by other factors not examined in this study, and partially, the effectiveness and efficiency variables are not significantly influence the quality of public services. Limitations: In this study, the limitation is observation time which is only 30 days. The number of samples is limited, which only 50 50  persons  from Population and Civil Registration Service of Palembang.